Pengelolaan Dana Zakat Produktif Untuk Pemberdayaan Mustahik Pada LAZISNU Ponorogo - Teguh Ansori (IAIN Ponorogo, 2018)
Abstract: This study aims to determine the management of productive zakat funds for the empowerment of mustahik in LAZISNU Ponorogo. The management of zakat funds should be supported by the role of professional amil, therefore the community can take the advantage on its impact of social-economic side. Potential zakat funds for the purpose of the community empowerment is reducing poverty. This qualitative descriptive research is intended to explain the distribution system of productive zakat funds in LAZISNU Ponorogo. The result showed that there are two forms of zakat funds distribution, namely consumptive and productive distribution. The first form of zakat distribution can be defined as providing zakat funds to mustahik without its empowerment. While the productive zakat distribution is the provision of zakat funds to mustahik and its empowerment. It can be done through several activities, namely, the provision of venture capital as well as the budget for education and training. Finally, it can be concluded that accurate data collection can be carried out by submitting proposal by candidates of mustahik to LAZISNU then they are identified by amil. Abstrak: Penelitian ini bertujuan mengkaji pengelolaan dana zakat produktif untuk pemberdayaan mustahik pada LAZISNU Ponorogo. Pengelolaan dana zakat harus didukung dengan peranan amil yang profesional agar dampak zakat secara sosial ekonomi dapat dirasakan oleh masyarakat. Dana zakat yang potensial dalam pemberdayaan masyarakat utamanya adalah dalam pengentasan kemiskinan. Sehingga distribusi dana zakat yang telah terkumpul tidak sembarangan. Penelitian ini adalah penelitian deskriptif kualitatif. Tujuan dari penelitian ini untuk memdeskripsikan sistem distribusi dana zakat produktif di LAZISNU Ponorogo. Dalam hal distribusi dana zakat ada dua kriteria, yakni konsumtif dan produktif. Distribusi zakat konsumtif adalah memberikan dana zakat kepada mustahik tanpa di ikuti pemberdayaan mutahik. Sementara distribusi zakat produktif adalah pemberian dana zakat kepada mustahik yang diikuti dengan pemberdayaan. Sifat pemberdayaan yang dilakukan bisa untuk pemberian modal usaha, juga bia dalam bentuk ketrampilan yang diwujudkan biaya pendidikan dan pelatihan. Penelitian ini berkesimpulan pendataan yang akurat dengan cara pengajuan proposal oleh calon mustahik kepada LAZISNU dan identifikasi mustahik oleh amil.